Eco-Teology: Implementasi Kelompok Sunda Wiwitan Dalam Mempertahankan Ekosistem - Adil, Muhammad adil muttaqin; , Sabrina Trias Safithry; Maretha Nur Safira Ainaya; Vania Bintang Aurora; Ikmal Ardiansyah5; Aditia Muhammad Noor (Universitas Nahdlatul Ulama Sunan Giri, 2025)
Ecotheology is the study that refers to the relationship between God, the Creator, and organisms in the terrain. Sunda Wiwitan is a former Sundanese belief system and its training came from the elders who empowered their successors to continue the religion. When you hear the word